Nyctalus noctula - Voon-Ching Lim; Rosli Ramli; Subha Bhassu; John-James Wilson (Zenodo, 2017)
Nyctalus noctula [Schreber, 1774] (?) Vespertilios noctula Schreber, 1774: 166, pl. 52; FRANCE (Collector unknown; Type unknown) [202]. Nyctalus noctula [8]. Common English name: Eurasian Noctule Barcode Index Number: DNA barcodes recorded as N . noctula are associated with BIN, BOLD: AAC 7411, but there are no DNA barcodes from Peninsular Malaysia. Remarks: Chasen [8] suggested that the species in Peninsular Malaysia may represents N . n . labiate = labiatus Hodgson, 1835 (type locality = Nepal) which also occurs in Pakistan and India [9]. N . n . labiatus is considered to be morphologically distinct from N . noctula and therefore, should be raised as a species [203]. The records of N . noctula from Peninsular Malaysia, if valid, may be referable to “labiatus” or “plancyi” [203]. IUCN status: Least Concern Recorded at: There is only one record of N . noctula in this region which is an old skin dated 1838 purchased in Singapore [204] but its origin remains doubtful [23]. Based on the purchased skin, Dobson [204] included Peninsular Malaysia in the distribution range of N . noctula , which was followed by Corbet and Hill [9] and Medway [23]. We could not find recent records for the species although it is thought to occur in Peninsular Malaysia [1, 10]. We found two old records which reported two specimens of Nyctalus sp. in a National Park, Pahang [87] and Ulu Langat Forest Reserve, Selangor [88]. However, there are no specimens deposited in the DWNP collection. N . noctula roosts in tree hollows and forages high above canopy [14, 23]. Published as part of Voon-Ching Lim, Rosli Ramli, Subha Bhassu & John-James Wilson, 2017, A checklist of the bats of Peninsular Malaysia and progress towards a DNA barcode reference library, pp. 1-65 in PLoS ONE 12 (7) on page 47, DOI:10.1371/journal.pone.0179555, http://zenodo.org/record/4251352